Efek pemberian ekstrak teh hijau (Camellia sinesis (L) O. Kuntze) var. Assamica terhadap total lemak tubuh dan profil lipid wanita dewasa overweight dan obesitas - Ernawati Hardani; Wiryatun Lestariana; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Overweight and obesity can cause high body fat total and lipid profile in the blood that brings risk for diseases to the bearer. Some studies on green tea extract supplementation have been undertaken to find out its effect on the fat reduction in children, men, and mice and the result showed a reduction in body fat, weight, appetite, and triglyceride level. This study uses green tea extract supplemented to overweight and obese women. Objective: To find out the reduction of body fat total and lipid profile (total cholesterol, triglyceride, LDL, HDL) in the blood of overweight and obese women personnel of Yogyakarta Municipal Health Office supplemented with green tea extract.Method: The study was randomized double-blinded control trial. The subject of the study was overweight and obese women of 35-55 years old personnel of Yogyakarta Municipal Health Office. Samples were 86 women randomly taken, comprising experiment group and control group, each of which consisting of 43 women. Each group had diet according to individual appetite. Both groups were given capsules of similar form and color but different ingredients: placebo and green tea extract. The experiment took three months. Blood was taken before and after the experiment to identify lipid profile (total cholesterol, triglyceride, LDL, HDL). Body fat total was examined using body fat analyzer. Data analysis used paired t-test.Results: Green tea extract supplementation could significantly reduce body fat total and insignificantly reduce cholesterol level, triglyceride, and LDL, significantly increase HDL in overweight and obese women.Conclusion: Green tea extract supplementation could reduce body fat total and increase HDL (p<0.005).